Identification of novel splice mutation in SMAD3 in two Cypriot families with nonsyndromic thoracic aortic aneurysm. Two case reports. Issue 9 (29th June 2020) - Keravnou, Anna; Bashiardes, Evy; Barberis, Vassilis; Michailidou, Kyriaki; Soteriou, Marinos; Tanteles, George A.; Cariolou, Marios A.
Abstract: Background: Thoracic aortic aneurysm and dissection (TAA/D) represents a potentially lethal disease group characterized by an increased risk of dissection or rupture. Only a small percentage (approximately 30%) of individuals with nonsyndromic familial TAA/D have a pathogenic variant in one of the genes that have been found to be associated with the disease. Methods: A targeted sequencing panel and direct sequencing approach were used to identify causative mutations in the index patients and other family members. Results: In this study we report two apparently unrelated Cypriot families with nonsyndromic familial TAA/D. The proband A is a female patient diagnosed with TAA/D and intracranial aneurysm and opted for an elective intervention. The proband B is a male patient who was diagnosed with TAA/D and underwent cardiac surgery. Sequencing analysis identified a novel splice site variant (c.871+1G>A) in SMAD3 which is shown to be associated with the disease. Analysis of mRNA from the patient's tissue confirmed aberrant splicing and exon 6 skipping. Conclusion: Our findings expand the mutation spectrum of variants that have been shown to be associated with nonsyndromic familial TAA/D. This study demonstrates the importance of a comprehensive clinical and genetic evaluation aiming at early diagnosis and intervention. Abstract : In this study we report two apparently unrelated Cypriot families with nonsyndromic familial thoracic aortic aneurysm and dissection associated with a novel variant in SMAD3. Analysis of mRNA from patients' tissue confirmed aberrant splicing and exon 6 skipping. This study demonstrates the importance of a comprehensive clinical and genetic evaluation aimed at early diagnosis and intervention.